Sugar consumption, sugar sweetened beverages and Attention Deficit Hyperactivity Disorder: A systematic review and meta-analysis. (September 2020) - Farsad-Naeimi, Alireza; Asjodi, Foad; Omidian, Mahsa; Askari, Mohammadreza; Nouri, Mehran; Pizarro, Ana Beatriz; Daneshzad, Elnaz
Highlights: Attention-deficit/hyperactivity disorder (ADHD) is an important neurobehavioral disorder in children and adolescence which may be affected by diet. The present study was conducted to evaluate the possible relationship between sugar consumption and ADHD. In total, seven studies (two cross-sectional, two case-control, and three prospective) with totally 25, 945 individuals were eligible to include in the current meta-analysis. This meta-analysis indicated a positive relationship between overall sugar and sugar-sweetened beverages consumption and symptoms of ADHD; however, there was heterogeneity among included studies. Abstract: Background: Attention-deficit/hyperactivity disorder (ADHD) is a significant neurobehavioral disorder in children and adolescence which may be affected by diet. Objective: To evaluate the possible relationship between sugar consumption and the development of symptoms of ADHD. Methods: In March 2020, an exhaustive systematic literature search was conducted using Google Scholar, PubMed, and Scopus. In this meta-analysis of observational studies, odds ratios, relative risks, hazard ratios, and their 95% confidence intervals, which was reported for ADHD regarding SSBS, soft drink consumption, and dietary sugars, were used to calculate ORs and standard errors. At first, a fixed-effects model was used to drive the overall effect sizes using log ORs and SEs. If there was any significant between-studies heterogeneity, the random-effects model was conducted. Cochran's Q test and I 2 were used to measure potential sources of heterogeneity across studies. The Newcastle-Ottawa scale was used to assess the quality of the included articles. Results: Seven studies, two cross-sectional, two case-control, and three prospective with a total of 25, 945 individuals were eligible to include in the current meta-analysis. The association between sugar and soft drink consumption and the risk of ADHD symptoms were provided based on the random-effects model (pooled effect size: 1.22, 95%CI: 1.04-1.42, P = 0.01) (I² = 81.9%, P heterogeneity < 0.0001). Conclusion: This meta-analysis indicated a positive relationship between overall sugar and sugar-sweetened beverages consumption and symptoms of ADHD; however, there was heterogeneity among included studies. Future well-designed studies that can account for confounds are necessary to confirm the effect of sugar on ADHD.